Critical Analysis of Pharmaceuticals Inventory Management Using the ABC-VEN Matrix in Dessie Referral Hospital, Ethiopia - Mohammed SA; Workneh BD (Dove Medical Press, 2020)
Solomon Ahmed Mohammed, Birhanu Demeke Workneh Department of Pharmacy, College of Medicine and Health Science, Wollo University, Dessie, EthiopiaCorrespondence: Solomon Ahmed Mohammed Tel +251910504378Email ahmedsolomon21@gmail.comIntroduction: Inventory management is a complex process that accelerates the probability of stock-out and overstocking if not tracked properly. Classification of drugs based on their criticality, cost burden, and in combination is important to make inventory decisions and optimize the quality use of scarce resources. This study analyzed the pharmaceutical inventory management systems of Dessie Referral Hospital using the ABC-VEN matrix for the years 2013 to 2017.Methodology: Cross-sectional study design was used to review logistic data retrospectively from health commodity management information system and manual records. Data were collected from January 1– 20, 2018 in Dessie Referral Hospital.Results: In the five-year ABC-VEN analysis, 310 (17%), 368 (20.18%), and 1146 (62.83%) items were class A, B, and C, while 610 (34.56%), 1125 (63.74%), and 30 (1.7%) of pharmaceuticals were V, E, and N, respectively. Among these, 139 (7.88%) and 339 (19.21%) of AV and CV pharmaceuticals utilized 43.52% and 2.89% of annual drug expenditures, respectively. Category I, II, and III pharmaceuticals also accounted for 43.68%, 54.79%, and 1.53% of items with their respective USD drug expenditure of 2,268,405.64 (84.49%), 411,961.18 (15.34%), and 4483.97 (0.17%). The pharmaceutical inventory cost projected to be 1,619,351.79 USD in 2025 and total cost (β= 10.68, p = 0.001), class A (β= 8.68, p = 0.001), class B (β= 1.27, p = 0.007), class C (β= 0.72, p = 0.03), and E items (β= 6.08, p = 0.01) were statistically significant with inventory cost.Conclusion: A huge amount of budget is invested in class A and category I, which pinpoints the need for strict inventory control to prevent wastage and accumulation of capital in buffer stocks. ABC-VEN analysis should be routinely performed before initiation of any new procurement for efficient use of scarce resources.Keywords: inventory management, ABC analysis, VEN analysis, ABC-VEN matrix